Long-Term Evaluation of Sumatriptan and Naproxen Sodium for the Acute Treatment of Migraine in Adolescents - McDonald, Susan A.; Hershey, Andrew D.; Pearlman, Eric; Lewis, Donald; Winner, Paul K.; Rothner, David; Linder, Steven L.; Runken, M. Chris; Richard, Nathalie E.; Derosier, Frederick J. (Headache, 2011)
Objectives.— To evaluate the long‐term safety, tolerability, effectiveness, impact on quality of life, and medication satisfaction of sumatriptan/naproxen sodium in the acute treatment of migraine headache in adolescents. Methods.— This 12‐month, multicenter, open‐label, safety study was conducted in adolescents (aged 12‐17 years) with an average of 2‐8 migraines/month typically lasting >2 hours untreated for >6 months prior to initiation. Subjects were instructed to treat migraines as early as possible and were allowed to rescue 2 hours post dose with a single dose of a naproxen‐containing product, over‐the‐counter pain reliever, or anti‐emetics. Subjects were advised not to take a second tablet of sumatriptan/naproxen sodium without at least a 24‐hour headache‐free period. Safety evaluations included adverse events, laboratory tests, and vital signs and electrocardiogram evaluation. Other evaluations included freedom from pain, quality of life, and medication satisfaction. Results.— Of the 656 subjects enrolled, 622 (95%) treated at least 1 migraine with sumatriptan/naproxen sodium, of which 435 (70%) and 363 (58%) completed 6 and 12 months of the study, respectively. Overall, there were 12,927 exposures to sumatriptan/naproxen sodium: on average 2.5 tablets were taken per month per subject. The most common treatment‐related adverse events were nausea (7%), dizziness (3%), muscle tightness (3%), and chest discomfort (3%). There were no deaths; 4 subjects had 5 serious adverse events (suicide attempt, hemolytic anemia and syncope, suicidal ideation, spontaneous abortion) unrelated to sumatriptan/naproxen sodium and resolved without sequelae. Seven percent of subjects discontinued participation in the study because of an adverse event; 5% of subjects discontinued due to lack of efficacy. Overall, 42% of the migraine attacks were pain‐free within 2 hours of treatment with sumatriptan/naproxen sodium, subjects reported improvements from baseline in 2 of 3 quality of life domains over time, and were generally satisfied with the efficacy and overall treatment at the end of the study. Conclusion.— In adolescent migraineurs, after up to 12 months and over 12,000 exposures to sumatriptan/naproxen sodium, there were no new or clinically significant findings in the safety parameters, including the frequency and nature of adverse events, as compared to the individual components or to the adverse event profile in adults. In addition, sumatriptan/naproxen sodium provided freedom from pain over time, improvements in quality of life and medication satisfaction.